A Descriptive Qualitative Study on the Use of Cake Application to Address Students’ Pronunciation Difficulties at MA Mirqotul Ulum - Arini Roihati Farha; Muhammad Hifdil Islam; Zainuddin Zainuddin (Universitas Pahlawan Tuanku Tambusai, 2026)
Accurate pronunciation is fundamental to the development of oral proficiency, as it directly governs the clarity and comprehensibility of verbal interaction; nevertheless, many EFL learners continue to encounter phonetic hurdles stemming from insufficient practice, a lack of corrective feedback, and interference from their native language. While existing scholarship has widely acknowledged the advantages of Mobile-Assisted Language Learning (MALL), most studies remain centered on broad language acquisition, leaving a gap in understanding how specific applications are utilized to resolve pronunciation challenges within localized educational settings. Consequently, this study examines the integration of the CAKE application in English pronunciation instruction and its role in mitigating students' speech difficulties at MA Mirqotul Ulum through a descriptive qualitative framework. Involving an English instructor and their students, data were gathered via classroom observations, semi-structured interviews, phonetic assessments, and documentation, then processed through an interactive model of data analysis. The findings demonstrate that CAKE fosters a self-directed learning environment through its speech recognition and 'Listen and Repeat' functionalities, which offer instantaneous evaluation and lead to observable progress in both segmental and suprasegmental elements, alongside bolstered student motivation and confidence. Ultimately, this research underscores the practical utility of mobile based interventions in pronunciation pedagogy and enriches the discourse on MALL by providing empirical evidence of a specialized application’s efficacy in an EFL context.